In vitro study of spontaneous motility and cholinergic responses in the human Hirschsprung's disease colon - Schulze, Felix; Lindert, Judith; Köhling, Rüdiger; Märzheuser, Stefanie; Kirschstein, Timo (Frontiers in Pediatrics, 2025)
BackgroundThe current standard treatment of Hirschsprung's disease (HD) involves complete resection of the aganglionic intestinal segment with routine rectal irrigation pre- and postoperatively. To date, our understanding of the underlying pathomechanisms is not sufficient to warrant modifying this therapeutic approach. Here, we utilized resected tissue specimens from children with HD to investigate spontaneous motility and cholinergic responses in circular muscle from both ganglionic and aganglionic colon in vitro.MethodsFull-thickness intestinal samples (from both aganglionic and ganglionic segments) were obtained intraoperatively from children with HD undergoing pull-through surgery. After removing the mucosal tissue and longitudinal smooth muscle, we prepared specimens consisting of circular muscle layer and submucosal tissue. These deafferentiated specimens were mounted in the organ bath to record isometric forces during spontaneous motility or following cholinergic stimulation.ResultsRegarding spontaneous motility, the basal tone was observed in all specimens, and phasic contractions were observed in 81% vs. 63% of ganglionic and aganglionic specimens, respectively. Both basal tone and phasic contractions were abolished in the presence of 40 mM EDTA indicating Ca2+ dependence, yet atropine (1 µM) had no effect on these measures. Increasing concentrations of the muscarinic receptor agonist carbachol raised the basal tone of ganglionic specimens, but significantly less potently in aganglionic tissue. In contrast, carbachol-evoked phasic contractions were still observed and even larger in aganglionic specimens than in ganglionic tissue.ConclusionsWe conclude that the circular muscle of aganglionic colonic segments retains the ability to establish a Ca2+-dependent and atropine-insensitive spontaneous motility similar to the circular muscle of ganglionic tissue. However, both tissue segments differed considerably in response to external cholinergic stimulation with significantly enhanced phasic-to-tonic contraction ratios in aganglionic specimens. These findings will help understand the persistent circular muscle contraction in aganglionic bowel which is still a major challenge in the preoperative HD management.